2014
DOI: 10.1099/jmm.0.067140-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Escherichia coli isolates from patients with urinary tract infections in Palestine

Abstract: Antibiotic resistance of Escherichia coli isolated from urinary tract infections (UTIs) is increasing worldwide. A total of 41 E. coli isolates were obtained from urine samples from hospitalized patients with a UTI in three hospitals in the northern districts of the West Bank, Palestine during March and June 2011. Resistance rates were: erythromycin (95 %), trimethoprimsulfamethoxazole (59 %), ciprofloxacin (56 %), gentamicin (27 %), imipenem (22 %), amoxicillin (93 %), amoxicillin-clavulanic acid (32 %), ceft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
16
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 22 publications
11
16
3
1
Order By: Relevance
“…In this present study, the maximum number (19 isolates) of urine carried 40% of MBLs producing gene which agreed with other study defined previously (Anago et al, 2015). Furthermore, a study in Indonesia in which sputum was the highest carriage of these genes (Karuniawati et al, 2013) (Adwan et al, 2014). In contrast, the higher resistant rate (82%) was observed in 2015 (Rezai et al, 2015) while 100% isolates were imipenem resistant (Liang et al, 2017) compared to this present study.…”
Section: Discussionsupporting
confidence: 91%
“…In this present study, the maximum number (19 isolates) of urine carried 40% of MBLs producing gene which agreed with other study defined previously (Anago et al, 2015). Furthermore, a study in Indonesia in which sputum was the highest carriage of these genes (Karuniawati et al, 2013) (Adwan et al, 2014). In contrast, the higher resistant rate (82%) was observed in 2015 (Rezai et al, 2015) while 100% isolates were imipenem resistant (Liang et al, 2017) compared to this present study.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the fact that, some of the antimicrobial agents in the study demonstrated substantial sensitivities, some uropathogens showed extremely high level of AMR, more especially to erythromycin 74/86 (86.0%). The Gram negative bacteria demonstrated 56/56 (100.0%) resistance to erythromycin, this finding is more similar to previous reports by Kyabaggu et al (2007); Kibret and Abera, (2011) and Adwan et al (2014). The Gram positive bacteria resistance to erythromycin of 18/30 (60.0%) reported in this study is more comparable to previous report by Kabugo et al (2016).…”
Section: Discussionsupporting
confidence: 90%
“…From these tables we can observe that studies conducted in non-con ict affected countries appeared to be slightly more focused in terms of site of infection under investigation compared to studies conducted in con ict affected countries, where in a substantial proportion of cases the site of infection was not speci ed, or the authors were analysing resistance pro les of bacteria isolated from a miscellanea of specimens. Publication bias was assessed for a sub-sample of ten studies which presented the proportion of ESBL producers among E. coli isolates on urinary samples, six of which were conducted in con ict-affected countries (45,54,59,75,114,159) and four in non-con ict settings (154,155,164,165). Figure 4 shows the funnel plots elaborated on the logarithm of the proportion of ESBL producers amongst E. coli isolates in urine samples in all studies, and in studies conducted in con ict and non-con ict settings separately.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%